Added Value of Canned Patin Fish as a Product of Patin Fish Agroindustry from South Sumatera - Beta Natalia; Elisa Wildayana; Riswani Riswani (Publikasi Penelitian Terapan dan Kebijakan, 2023)
The South Sumatra Provincial Government has provided processed food canning production facilities for developing downstream food industry products produced by food MSMEs in South Sumatra Province. Information related to the added value obtained from the canning business of processed food products and their marketing conditions is still not widely known. The purpose of this study is to calculate income and analyze the added value of fresh Patin fish in canned Patin fish Pindang products. This research was conducted at the location of the Regional Research and Development Board processed food canning production facility in South Sumatra Province with purposive sampling, namely canned Patin fish Pindang with the brand “Tangkep” processed with canning facilities provided by the South Sumatra Provincial Government through Regional Research and Development Board. The Hayami method was used for the calculation of added value analysis for canned Patin fish Pindang products. The results showed that the profits obtained based on added value analysis, namely 51% of the sales of the products, were received by business actors, namely the Tangkep MSMEs. It can be concluded that the processing of fresh Patin fish into canned Patin fish Pindang products was classified as profitable with high added value because the value-added ratio was > 40%.